58th AIAA/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2017
DOI: 10.2514/6.2017-1118
|View full text |Cite
|
Sign up to set email alerts
|

Panel Flutter Analysis and Optimization of Composite Tow Steered Plates

Abstract: The flutter behavior of tow steered composite panels, in which the fiber placement follow curvilinear trajectory, is evaluated. A simple structural model based on Ritz method combined with supersonic aerodynamic piston theory is used to analyze the aeroelastic behavior. Classical lamination plate theory and symmetric stacking sequence are used and the fiber trajectories are defined by Lagrange interpolation functions. The flutter stability boundaries for optimal conventional (constant stiffness laminates) layu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…2). Calculating the far field distance d f using df =2 (D 2 )/λ ( 1 ) where D is the largest antenna aperture dimension (164 mm,) and λ is the wavelength (144.8 mm at 2.670 GHz), yields d f = 371.4 mm. This establishes that the 510 mm antenna-to-tape distance for this experiment is in the far field.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Calculating the far field distance d f using df =2 (D 2 )/λ ( 1 ) where D is the largest antenna aperture dimension (164 mm,) and λ is the wavelength (144.8 mm at 2.670 GHz), yields d f = 371.4 mm. This establishes that the 510 mm antenna-to-tape distance for this experiment is in the far field.…”
Section: Methodsmentioning
confidence: 99%
“…Because a side effect of reducing structural weight is an increased susceptibility of wings to enter into flutter conditions, methods of reducing the onset of flutter are concurrently being explored. One method of reducing the probability of flutter onset in a CFRP wing structure is to aeroelastically "tune" the structural characteristics via carbon fiber tow steering [1,2]. Both flutter and gust response can be modified using tow steering methods [3].…”
Section: Introductionmentioning
confidence: 99%
“…Guimaraes et al. 11 studied the flutter behavior of tow-steered flat thin composite panels with curvilinear fiber placements using the Ritz method. The flutter stability boundaries of optimal conventional layups (constant stiffness laminates) and nonconventional steered panels (variable stiffness laminates) were extracted and compared.…”
Section: Introductionmentioning
confidence: 99%
“…The use of linearly varying fiber angle per bay, for stiffened plates, has also been investigated, and again it has been shown that varying the fiber angles leads to better performance [7,8]. Direct parametrisation of the tow paths using Lagrangian polynomials [9,10,11] Lobatto-Legendre polynomials [12,13], Bezier curves [14,15,16], splines [17,18], B-splines surfaces [19] and NURBS (Non-Uniform Rational B-Splines) [20] have also been used. Constant curvature paths have been extensively applied for flat panels and for cylindrical and conical shells [21,22,23,24,25], as the curvature constraint evaluation is simplified.…”
Section: Introductionmentioning
confidence: 99%